2012
DOI: 10.1136/jnnp-2012-302420
|View full text |Cite
|
Sign up to set email alerts
|

Is psycho-physical stress a risk factor for stroke? A case-control study

Abstract: Compared with healthy age-matched individuals, stressful habits and type A behaviour are associated with high risk of stroke. This association is not modified by gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 33 publications
0
24
0
2
Order By: Relevance
“…Health-related QoL has been reported to independently predict mortality following Coronary Artery Bypass Grafting (CABG) 3 , Myocardial Infarction (MI) 4,5 , heart failure 6 , Diabetes Mellitus 78 , and Hemodialysis 9 . Egido et al found that psychosocial stress predicted stroke in a small case-control study, implying that QoL is a significant causative role 1011 . Socioeconomic factors influencing QoL such as unemployment or multiple job losses, may be significant risk factors for acute MI and stroke 121314 .…”
Section: Introductionmentioning
confidence: 99%
“…Health-related QoL has been reported to independently predict mortality following Coronary Artery Bypass Grafting (CABG) 3 , Myocardial Infarction (MI) 4,5 , heart failure 6 , Diabetes Mellitus 78 , and Hemodialysis 9 . Egido et al found that psychosocial stress predicted stroke in a small case-control study, implying that QoL is a significant causative role 1011 . Socioeconomic factors influencing QoL such as unemployment or multiple job losses, may be significant risk factors for acute MI and stroke 121314 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some sort of biological rationale suggests perhaps in acute stressful situations a person could be at risk of stroke. According to studies by Egido et al (2012), compared with healthy age-matched individuals, stressful habits and type A behavior are associated with high risk of stroke. This association is not modified by gender.…”
Section: Discussionmentioning
confidence: 99%
“…The recent stress in patient's life could be a significant risk factor for stroke in young population. A case control study by Egido et al 8 disclosed that stressful habits are significantly associated with high risk of stroke. Other case reports conclude that oral contraceptives may be implicated as a cause of basilar artery thrombosis 7 9.…”
Section: Discussionmentioning
confidence: 99%